Community advisory boards and research ethics in low-income and middle-income countries: a scoping review. (October 2018) - Zhao, Yang; Fitzpatrick, Thomas; Wan, Bin; Day, Suzanne; Mathews, Allison; Tucker, Joseph D
Abstract: Background: Community advisory boards (CABs) are no longer limited to high-income countries (HICs); they play an increasing role in research in low-income and middle-income countries (LMICs). Much work has examined the establishment and implementation of CABs in HICs, but less is known about CABs in LMICs. The purpose of this scoping review is to study the operation of CABs in LMICs and to discuss the implications for research ethics. Methods: We searched five databases (PubMed, Embase, Global Health, Scopus, and Google Scholar) for publications describing or evaluating CABs in LMICs. Two researchers independently reviewed articles for inclusion. Data relating to the following aspects of CABs were extracted from included publications: publication date, country, financial support, research focus, responsibilities, and challenges. Thematic analyses were used to summarise textual data describing challenges. Findings: Our search yielded 2005 citations, 83 of which were deemed eligible for inclusion. Most studies (65) were published between 2010 and 2017. Upper-middle-income countries, as defined by the World Bank, were more likely to have CAB studies, and of these South Africa (17), China (8), and Thailand (7) had the greatest numbers. Among the 34 CABs whose funding sources were reported, the US National Institutes of Health was the main source of financial support for CABs. Most CABs (53 of 88) in our sample advised on HIV research. Thirty-four studies reported how CABs influenced the informed consent process for clinical trials or other aspects of research ethics. CAB responsibilities were related to clinical trials (87 of 88), including educating local communities about research activities, and promoting the ethical conduct of research. The challenges faced by CABs included incomplete ethical regulations and guidance, limited knowledge of science among CAB members, unstable and unbalanced power relationships between researchers and local communities, poor CAB management, competing demands for time that limited participation in CAB activities, and language barriers between research staff and community members. Interpretation: CABs may be a useful instrument for increasing community engagement and improving the ethical conduct of research in LMICs. Our study identifies several challenges faced by CABs in LMICs. These findings can help inform training and related activities to enhance CABs in LMICs. Funding: This work was supported by the National Institutes of Health (National Institute of Allergy and Infectious Diseases [NIAID]) number 1R01A108366.